Energy storage capacity optimization strategy for combined wind storage system - Qingsheng Li; Zhen Li; Zhaofeng Zhang; Yibin Tao; Ruien Bian (Energy Reports, 2022)
The rapid development of wind power has imposed many challenges on the operation of the power system. Energy storage system has broad application prospects in promoting wind power to the grid. However, the high price of the energy storage restricts the development of the combined wind energy-storage system. In order to deal with the power fluctuation of the large-scale wind power grid connection, we propose an allocation strategy of energy storage capacity for combined wind-storage system considering the wind power output volatility and battery storage system’s own operational constraints. The model aims to maximize the annual avenue of the cogeneration system, which allows for the investment fee, operation and maintenance fee and penalty cost of the combined system. The calculation results validate the effectiveness of the optimal allocation strategy.